The planning of the actions of the educational inspection - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2019)
The educational administrations regulate the structure and functioning of their organs in their respective territorial areas for the performance of the education inspection, being the action plans which can guarantee the fulfillment of these functions. In general, these plans have a structure structured by objectives and actions that mark their lines of work and performance criteria. They also have different levels (regional and provincial, multi-annual and annual) that guide the performance of the work and with a prioritization of actions to achieve the previously formulated objectives. Therefore, the action plans project the work over a period of time and provide for the resources with the ultimate goal of ensuring compliance with the laws, the guarantee of rights and the observance of the duties of those who participate in the teaching processes and learning, the improvement of the education system and the quality and equity of education, as established in article 148.2 of the LOE.